A influência do capital social no compartilhamento do conhecimento entre empresas situadas em parques científicos e tecnológicos em diferentes culturas nacionais - Steffen, Mário Oscar (2019)
Knowledge is one of the most important resources of companies. The pressure from customers and competitors makes products and services obsolete quickly. An alternative to accelerate the process of creating new products and services is to look for other companies to share the knowledge of all, to meet the demands of the market. Knowledge can also be in universities, which have resources such as laboratories and researchers that can collaborate to meet the needs of companies. Having access to money-giving investors and management expertise allows companies to devote their efforts to better serve their clients. The science and technology parks are areas of innovation in which companies, universities and investors are present and which offer physical resources and knowledge so that companies can develop. The environment of scientific and technological parks allows the integration between companies, knowledge and capital. Park and business managers should be aware of how companies relate, how collaborative networks form, what kind of knowledge they need, how corporate culture interferes with relationship rules, and how to create an ecosystem in which there is trust between companies. The objective of this work is to analyze how the companies of science and technology parks form and use their networks of contacts and what the influence of the national culture in these relationships. To achieve these objectives, data were collected from companies located in science and technology parks in Brazil and Spain. Managers of 88 companies and managers of five technology parks in Brazil and seven in Spain were interviewed, in order to analyze if the initiatives of park managers and companies reach their purposes of integration and generation of knowledge. Responses from 217 questionnaires from employees of science and technology parks companies about how they share knowledge and how they relate to the ecosystem of the parks were analyzed. The combination of interview results and questionnaires sheds light on the context of the relationship between park companies, which has not yet been studied by the academy. The results also serve to managers of science and technology parks companies to decide on how to take advantage of park resources and for park managers to understand and focus their efforts on what really matters to businesses while respecting cultural particularities.